The Mediating Role of Partner Selection in the Association Between Transactional Sex and HIV Incidence Among Young Women - Meghna Ranganathan, PhD; Kelly Kilburn, PhD; Marie C.D. Stoner, PhD; James P. Hughes, PhD; Catherine MacPhail, PhD; Francesc Xavier Gomez-Olive, MD, PhD; Ryan G. Wagner, PhD; Kathleen Kahn, PhD; Yaw Agyei, MPH; Audrey Pettifor, PhD (My University, 2019)
Objective: In sub-Saharan Africa, transactional sex is associated with an increased risk of HIV infection in adolescent girls and young women, but the mechanisms for this relationship remain unclear. We hypothesize that young women who report transactional sex may have multiple partners and older partners, thereby increasing their HIV risk. Setting: We used longitudinal data from the HPTN 068 trial in rural South Africa where young women aged 13–20 who were HIV-negative at enrolment (n = 2362) were followed approximately annually for up to 6 years. Methods: We used the parametric g-formula to estimate the total effect of time-varying, frequent transactional sex (receipt of gifts/money at least weekly versus monthly or less) on HIV incidence and the controlled direct effect for mediation in a simulated cohort using 20,000 bootstrapped observations. We calculated rates and hazard ratios (HRs) over the entire study period. Results: The HR for the total effect of frequent transactional sex on HIV incidence was 1.56 (95% confidence interval: 1.28 to 1.85). However, this effect was mediated by partner age (>5+) and number of partners (>1) and the HR was attenuated to 1.09 (95% confidence interval: 0.90 to 1.28) when setting both partner age and partner number constant. Conclusion: Both partner age difference and partner number mediate the relationship between transactional sex and incident HIV infection. Through this mediation analysis, we provide important longitudinal evidence to suggest that young women who engage in frequent transactional sex select multiple partners, often older male partners that may be part of higher risk sexual networks.